Let us teach for real! : A plea for traditional teaching (Transactions of the Association of European Schools of Planning, 2019)
Before we even noticed, electronic devices and the internet have invaded our lives and our universities. Far from being just an instrument, they change the way we teach, whether we want it or not. Unfortunately, instead of helping, they carry negative effects, well documented by research in psychology, psychiatry and neuroimaging over the last decade. They affect our attention, our memory, and our social skills. Without even being aware of it, we are playing the Sorcerer’s Apprentice. Since 2011, the author has banned the digital and reinvigorated traditional teaching methods: a demanding, yet hugely rewarding experience. The present paper is a vibrant plea by a scholar to fellow scholars: let us get rid of the virtual! Let us teach for real!
Keywords: Planning education; learning methods; tech-free teaching